Hubungan Penggunaan Media Sosial dengan Tingkat Kepekaan Sosial di Usia Remaja - E.B., Gita Aprinta; S.W., Errika Dwi (Jurnal The Messenger, 2017)
Social media could improve the deployment of information and communication among users, including teenagers user. However, to be considered is whether the intensity of high social media usage among teens can reduce their social skills, as teens tend to become more individualized. The study was conducted using quantitative methods that involving 145 respondents, who attend in public and private schools, within 1-15 km of study range location. This study done based on the Uses and gratification theory as the grand theory. Other theory which used in this study is media dependency theory, in order to see how dependent the user on the use of social media. The results shows that the more often user access to social media, the more frequently the information search is done as a fulfillment of the information, which will triggered the concern of environment as well as the form of social consciousness.